Pengaruh Ukuran Perusahaan, Tipe Auditor, Profitabilitas, dan Leverage Terhadap Pengungkapan Modal Intelektual (Studi Pada Perusahaan di Bidang Infrastruktur, Utilitas, dan Transportasi yang Terdaftar di BEI Tahun 2018-2019) - Elsya Ajza Dewi; Aida Nahar (Jurnal Rekognisi Akuntansi, 2020)
This study is to analyze the effect of company size, industry type, auditor type, profitability and leverage on intellectual capital disclosure (Study on Infrastructure, Utilities, and Transportation Companies listed on the IDX in 2018-2019). The population in this study are Companies in the Infrastructure, Transportation and Utilities that are listed on the IDX in 2018-2019, as many as 104 companies. The sampling technique used was the Saturated Sampling (Census Sampling) method, that is, the total population was used as the research sample. Data analysis methods are descriptive statistical analysis, classical assumption test, regression analysis, and hypothesis testing. The results of this study indicate that there is no effect of industry type, profitability, and leverage on intellectual capital disclosure. However, firm size has a negative effect and the type of auditor has a positive and significant effect on intellectual capital disclosure